PRIORITY DIRECTIONS AND LEGAL BASES OF MODERNIZATION OF THE TAX SYSTEM OF THE REPUBLIC OF UZBEKISTAN - Buranova Lola Vakhobovna; Sadikov Iskandar Gayratovich; Kushbakov Mukhammadjon Shodiyor ugli (European Science Publishing, 2025)
This article is devoted to the prospects of reforming the tax system in the context of globalization. It examines the scientific justification of the tax system and identifies systemic problems that hinder the dynamic economic growth of the Republic of Uzbekistan. The scientific analysis is carried out on the basis of studying the tax system and the share of each tax in the state budget revenues of the Republic of Uzbekistan, possible prospects for their solution and the current conditions for its development.
Keywords: Tax system, tax burden, VAT, excise tax, customs duties, income tax, water resources tax, mineral resources tax, personal income tax, property tax, land tax, turnover tax